Filling Defect of Ipsilateral Transverse Sinus in Acute Large Artery Occlusion - Chen, Yi; Zhang, Sheng; Yan, Shenqiang; Zhang, Meixia; Zhang, Ruiting; Shi, Feina; Liebeskind, David S.; Parsons, Mark; Lou, Min (Frontiers in Neurology, 2022)
Background and purpose: Cerebral venous systems play a key role in regulating stroke outcome. We aim to elucidate the effect of transverse sinus (TS) filling patterns on edema expansion and neurological outcome in patients with acute large artery occlusion (LAO). Materials and methods: We recruited consecutive patients with acute M1 middle cerebral artery and/or internal carotid artery occlusion who underwent pretreatment computed tomographic perfusion (CTP). On the reconstructed 4-dimensional computed tomographic angiography derived from CTP, filling defect of ipsilateral transverse sinus (FDITS) was defined as the length of contrast filling defect occupying at least half of the ipsilateral TS. Unfavorable outcome was defined as having modified Rankin Scale score 3-6 at 3 months. Results: A total of 318 patients were enrolled in final analysis and 70 (22.0%) patients had baseline FDITS. The presence of FDITS was associated with baseline NIHSS (OR 1.119; 95% CI, 1.051-1.192; P<0.001) and poor arterial collaterals (OR 3.665; 95% CI 1.730-7.766; P=0.001). FDITS was also associated with 24-hour brain edema expansion (OR 7.188; 95% CI, 3.095-16.696; P<0.001) and 3-month unfavorable outcome (OR 8.143; 95% CI 2.547-26.041; P<0.001) independent of arterial collateral status. In subgroup analysis of FDITS patients who received reperfusion therapy, no significant difference was found in the rate of edema expansion and unfavorable outcome between non-reperfusion and reperfusion subgroup (both P>0.05). Conclusion: FDITS was associated with edema expansion and unfavorable outcome irrespective of baseline arterial collateral status in patients with acute LAO, indicating that FDITS may be an important stroke-related prognostic imaging marker.